HIPOTESIS PENINGKATAN PENDAPATAN PETANI: PERSPEKTIF ISLAM - Riyardi, Agung (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2002)
Optimizing the land can increase the small farmer income. That is, as the classical economic scale of farming state: "bigger land, bigger production (and the income) ". According to this principle, Islamic economist argue that there is two Islamic model, first the land leasing and second unity of the ownership and cultivating of the land. Besides, the models are the alternative of the land reform model. But the second model, the unity is the best alternative both for increasing the income and land reform